Distribution of Emergency Department Encounters and Subsequent Hospital Admissions for Children by Child Opportunity Index. - Ramgopal, Sriram; Attridge, Megan; Akande, Manzilat; Goodman, Denise M.; Heneghan, Julia A.; Macy, Michelle L. (Academic Pediatrics)
Objective: To evaluate differences in emergency department (ED) utilization and subsequent admission among children by Child Opportunity Index (COI). METHODS: We performed a cross-sectional study of pediatric (<18 years) encounters to 194 EDs in Illinois from 2016 to 2020. Each encounter was assigned to quntiles of COI 2.0 by postal code. We described the difference in the percent of encounters between lower (Very Low and Low) and higher (Very High and High) COI overall and among diagnoses with overrepresentation from lower COI groups. We evaluated the association of diagnosis with COI in ordinal models adjusted for demographics. Results: There were 4,653,026 eligible ED encounters classified by COI as Very Low (28.6%), Low (24.8%), Moderate (20.3%), High (15.6%), and Very High (10.8%) (difference between low and high COI encounters 27.0%). Diagnoses with the greatest difference between low and high COI were eye infection, upper respiratory tract infections, and cough. The COI distribution for children admitted from the ED (n = 140,298) was 29.1% Very Low, 19.3% Low, 18.2% Moderate, 17.7% High, and 15.7% Very High (percent difference 15.1%). Diagnoses with the greatest differences between low and high COI among admitted patients were sickle cell crisis, asthma, and influenza. All ED diagnoses and 7/12 admission diagnoses were associated with lower COI in multivariable ordinal models. CONCLUSIONS: Children from lower COI areas are overrepresented in ED and inpatient encounters overall and within certain diagnosis groups. Further research is required to examine how health outcomes may be influenced by the structural and contextual characteristics of a child's neighborhood.